2014
DOI: 10.1890/es14-00051.1
|View full text |Cite
|
Sign up to set email alerts
|

Managing temperate forests for carbon storage: impacts of logging versus forest protection on carbon stocks

Abstract: Abstract. Management of native forests offers opportunities to store more carbon in the land sector through two main activities. Emissions to the atmosphere can be avoided by ceasing logging. Removals of carbon dioxide from the atmosphere can be increased by allowing forests to continue growing. However, the relative benefits for carbon storage of managing native forests for wood production versus protection are contested. Additionally, the potential for carbon storage is impacted upon by disturbance events, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 102 publications
(82 reference statements)
3
80
2
3
Order By: Relevance
“…Their value, however, was in good agreement with the sub-regional estimates provided by the local State Forest agency (VicForests) for pure mountain ash stands in the Central Highlands of Vic (approximately 287 t C/ha) [19]. Keith et al [41] calculated stem and branch volumes using an allometric equation for mountain ash [28] based on tree diameter (accounting for stem buttressing and internal wood decay), and multiplied by wood density and carbon concentration. There was good agreement between the AGC reported in our study and those in [41] for 1939 regrowth mountain ash stands.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Their value, however, was in good agreement with the sub-regional estimates provided by the local State Forest agency (VicForests) for pure mountain ash stands in the Central Highlands of Vic (approximately 287 t C/ha) [19]. Keith et al [41] calculated stem and branch volumes using an allometric equation for mountain ash [28] based on tree diameter (accounting for stem buttressing and internal wood decay), and multiplied by wood density and carbon concentration. There was good agreement between the AGC reported in our study and those in [41] for 1939 regrowth mountain ash stands.…”
Section: Discussionsupporting
confidence: 53%
“…Keith et al [41] calculated stem and branch volumes using an allometric equation for mountain ash [28] based on tree diameter (accounting for stem buttressing and internal wood decay), and multiplied by wood density and carbon concentration. There was good agreement between the AGC reported in our study and those in [41] for 1939 regrowth mountain ash stands. However, the productivity of the mountain ash study site was higher than typical 1939 mountain ash regrowth stands.…”
Section: Discussionmentioning
confidence: 99%
“…Keith et al (2009) suggested that Mountain Ash forests are the most carbon-dense forests on earth. They store vast amounts of carbon, particularly when they have not been disturbed by industrial logging (Keith et al 2014). As in many forest types globally, large old trees contribute a significant proportion of the total carbon biomass stored in individual forest stands.…”
Section: Case Study Of Large Old Trees In Victorian Montane Ash Forestsmentioning
confidence: 99%
“…This has other key advantages; for example, a larger old growth estate will have fire suppression benefits as well as creating potentially suitable post-fire habitat for animals such as Leadbeater's Possum Lindenmayer et al 2015). In addition, an increased old growth forest estate would have major ecosystem service benefits such as increased levels of carbon storage (Keith et al 2014) and water production (Vertessy et al 2001;Viggers et al 2013).…”
Section: Challenges To the Management And Conservation Of Large Old Tmentioning
confidence: 99%
“…More recently, evidence is accumulating that forest management (defined as forest remaining forest but undergoing tree or other biomass removal, clear-cuts, fire suppression and/or species change) may also have substantial effects on the atmospheric CO 2 concentration (Hudiburg et al, 2011(Hudiburg et al, , 2013Keith et al, 2014) in addition to affecting the surface climate through changes in albedo, evapotranspiration and surface roughness (Jackson et al, 2005(Jackson et al, , 2008Randerson et al, 2006;Rotenberg and Yakir, 2010;Luyssaert et al, 2014;Otto et al, 2014). Hence, to fully understand the impact of the large-scale application of forest management, taking into consideration only the carbon balance is not sufficient.…”
Section: Introductionmentioning
confidence: 99%